If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/2(3x+3)=2(1-3x)+13
We simplify the equation to the form, which is simple to understand
3/2(3x+3)=2(1-3x)+13
Simplifying:
+1.5*(3x+3)=2*(1-3x)+13
Reorder the terms in parentheses
+(+4.5x+4.5)=2*(1-3x)+13
Remove unnecessary parentheses
+4.5x+4.5=+2+*(+1-3x+)+13
Reorder the terms in parentheses
+4.5x+4.5=+(+2-6x)+13
Remove unnecessary parentheses
+4.5x+4.5=+2-6x+13
We move all terms containing x to the left and all other terms to the right.
+4.5x+6x=+2+13-4.5
We simplify left and right side of the equation.
+10.5x=+10.5
We divide both sides of the equation by 10.5 to get x.
x=1
| 3x+22=3+6x-5 | | 4(5+x)=20 | | 7(a+b)=7a | | 3(2x+9)=6x | | 90z+10z=100 | | 5a+10a=20 | | 1y+1=x | | 2x^3-x^2-20x+10=0 | | 10x+13=6x+113 | | 66-3x=15x+22 | | x*x+3=28 | | 97-3x=33x+17 | | 18P-0= | | 134-10x=9x+18 | | 4x=36+3x | | -66.66y=22 | | 22=15x | | 25-5= | | -0.003x^2+0.577x+2=0 | | 67x-45y=56x+8y | | 6x^2-19x=14 | | 219-5x=31x+19 | | m^2-10m+18=0 | | 9+-8x=32+-15x | | 11x-19=6x+11 | | 2-(6-2x)=0 | | 12x-15y=80 | | 2x^4-9*x^3-4x^2-5x=0 | | x*3+x^2-8*x-8=0 | | 7y-5=3x+23 | | 4(x+1)-3(x-3)=25 | | -7x+3x^2+2=0 |